Between the Politics of History and Practice: Ukrainian Struggles with the Past. The Example of the Permanent Exhibition of the National Museum of the History of Ukraine in the Second World War - Gontarska, Olga (Institute of National Remembrance Review, 2019)
In 2015, as a result of implementing the Ukrainian decommunisation laws, the official name of the Museum of the Great Patriotic War was changed to the National Museum of the History of Ukraine in the Second World War. The current exhibition at the museum depicts internalisation of Soviet myths in Ukraine as well as the problem of no explicit guidelines from state authorities regarding an official narrative. Also, developing a new concept of a museum dedicated to the history of Ukraine in the Second World War has been impeded by the ongoing war in the eastern part of the country. This paper discusses mutual relations and mismatches between Ukraine’s politics of history and museum practices. The change of the latter is much more languid and complex than in the case of merely changing street names or dismantling old monuments and erecting new ones.